Riskio: A Serious Game for Cyber Security Awareness and Education. Issue 95 (August 2020) - Hart, Stephen; Margheri, Andrea; Paci, Federica; Sassone, Vladimiro
Abstract: Cyber attacks are increasing in number and sophistication, causing organisations to continuously adapt management strategies for cyber security risks. As a key risk mitigation policy, organisations are investing in professional training courses for their employees to raise awareness on cyber attacks and related defences. Serious games have emerged as a new approach that can complement instruction-led or computer-based security training by providing a fun environment where players learn and practice cyber security concepts through the game. In this paper we propose Riskio, a tabletop game to increase cyber security awareness for people with no-technical background working in organisations. Riskio provides an active learning environment where players build knowledge on cyber security attacks and defences by playing both the role of the attacker and the defender of critical assets in a fictitious organisation.